Health Anxiety and Its Correlates in the General Chinese Population During the COVID-19 Epidemic - Jia Luo (Frontiers Media S.A., 2021)
Background: The novel coronavirus disease 2019 (COVID-19) pandemic has had an adverse impact on the mental health of the general population. This study aimed to investigate the prevalence and correlates of health anxiety (HA) in the general Chinese population to inform psychological interventions in COVID-19-affected areas.Methods: We conducted an online survey of the general population in mainland China between 6 and 17 February 2020 (N = 1,450, 69.79% female; mean age = 37.5 ± 9.1 years). The Whiteley Index-7 (WI-7), COVID-19 knowledge quiz (CKQ), Generalised Anxiety Disorder scale (GAD-7), Patient Health Questionnaire Depression Scale (PHQ-9), and socio-demographic information were surveyed using the Questionnaire-Star program.Results: The prevalence of HA, depression and anxiety were 47.3, 31.3, and 35.7%, respectively. The WI-7 score showed a significant association with age, education level, income, occupation, chronic disease and daily time focused on COVID-19. On binary logistic regression analysis, individuals with masters or higher qualification degree [odds ratio (OR) = 0.632)], older age (OR = 0.981), 2-4 h daily time focused on COVID-19 (OR = 0.684), healthcare workers (OR = 0.749, p = 0.046) and those with more COVID-19 related knowledge (OR = 0.785) showed a significantly negative association with HA. Chronic disease (OR = 1.962), depression (OR = 1.05) and anxiety (OR = 1.228) were significant risk factors for HA.Conclusions: HA was highly prevalent among the general population during the early stages of the COVID-19 outbreak. More than two-fifths of the respondents had obvious HA. Chronic disease, depression and anxiety were risk factors for HA; psychological interventions offered during the pandemic should pay particular attention to these individuals.